Quản trị lợi nhuận và nợ: Bằng chứng từ các công ty niêm yết ở Việt Nam - Nguyễn Công , Phương; Phạm Nguyễn Đình , Tuấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
The article employs the D-GMM estimator on a sample of 1,349 companies listed on the Vietnamese stock exchange during the period 2010–2018 forming into 10,130 observations. The article aims to examine the relationship between debt and earnings management in Vietnam, especially, the authors also explore the influence of debt maturity and debt sources (banks and bonds) on accrual-based earnings management. The research results show that managers make adjustments to increase earnings as the companies have a large short-term debt or debt balance increased over the previous year. On the contrary, earnings are adjusted to decrease as the companies have high long-term debt. In addition, the bank debt is no longer plays as a supervisory role as expected and managers tend to adjust the increase of earnings with a high level in case of large outstanding debt and increase over the previous year. Finally, the results show that the impact of debt on earnings management in long-term, whereby the level of earnings management is high under pressure of debt.